UPACARA POMALOANA MATE (MALAM KEMATIAN) BAGI ORANG BUTON (Studi di Kelurahan Kadolokatapi Kecamatan Wolio Kota Bau-Bau) - Siti Sahrani; La Ode Dirman; Ajeng Kusumawardhani (SANGIA: Jurnal Penelitian Arkeologi, 2018)
The research questions are (1) how is the process of pomaloana mate ritual for Butonese especially in the village of Kadolokatapi?, (2) what values are contained in the pomaloana mate ritual?, and (3) what is thesymbolic meaning contained in the implementation of the pomaloana mate ritual for the Butonese in the village ofKadolokatapi, town of Bau-Bau? The results of this study show several things. The first is the process ofceremony pomaloana mate for the Butonese, especially in the village of Kadolokatapi. This ceremony is theconductor for someone who entered the last life cycle, that is death. The ceremony includes two stages, namelypreparation and execution. Some things to be prepared in this ritual are, ie Al-Qur'an, incese, and offerings suchas waje, onde-onde, sanggarana hole, sanggarana kauwi-uwi, newasa, and bolu which are prepared in trays.This offer is presented as a requirement to perform a tradition for the grieving family and Buton Wolio communitygroup. Second is the value contained in this ceremony that is the value of education, ethical values, and religiousvalues. The second research result is the meaning of the pomaloana mate ritual symbolized from offerings in the ceremony.